ANALISIS KUANTITAS DAN HITUNG JENIS LEUKOSIT PADA PETUGAS RADIOLOGI DI BALAI BESAR KESEHATAN PARU MASYARAKAT (BBKPM) MAKASSAR - Suciyani Suciyani; Nurlia Naim; Zulfian Armah (Media Kesehatan Politeknik Kesehatan Makassar, 2017)
The Radiology Officer is one of the groups that has a risk to the danger of radiation exposure and it caused of the healthy in the certain level. Then, it could cause the Chronis disease until with the death. The effect of Chronis could appear in years later. Indicator of Hematopoietic commonly used as radiation exposure. It was differential count leukocyte, lymphocyte, absolute count, neutrophil, platelet and erythrocyte. The disturbance of hematopoitic system is caused radiation exposure that the effecting of the amount erythrocytes decreased as sensitivity and the life expectancy, which was the lymphocyte reacted firstly. It is followed by granulocyte, thrombocyte, and erythrocyte. The aim of this research is to know the quantity and differential count leukocyte with radiology officer. The kind of this research was descriptive research through quantity and differential count leukocyte with the radiology officer. There were 7 samples on 24 of February 2017 until 4 March 2017 in Balai Besar Kesehatan Paru Masyarakat Makassar. The quantity of the research with the radiology office in BBMK Makassar was 85,71% normally and it increased (14,29%) while the differential count leukocyte was 100% basofil in the amount of normal, 42,86% eosinophil increased, 14,29% neutrophil decreased, 14,29% lymphocyte increased, 14,29% monocyte decreased and 14,29% monosit increased. It should be more increased the effecting of dangerous radiation and the using of personal protective equipments should be increased based on the regulation of Bapeten number 8 at 2011 and radiology officer should be more attention to the nutritional and their healthy.Keywords: Quantity of Leukocyte, Differential Count Leukocyte, The Radiology Officer